Literary response and attitude toward reading fiction in secondary education: Trends and predictors - Van Schooten, Eric; De Glopper, Kees (L1-Educational Studies in Language and Literature, 2006)
The present article synthesizes the results of four studies that concern attitudes towards reading fiction and the literary response of students in secondary education. Both cross sectional and longitudinal data sets were created with the cross sectional data used for establishing ‘model fit' of both the attitude model and the literary response model. Relations between different components of both models used are charted among reading behavior and relations between model components and student characteristics. The longitudinal data is used to establish trends in attitude and response. Also relations between student characteristics and characteristics of literary education lessons on the one hand and trends in attitude and literary response scores on the other are examined. Results indicate that both the attitude and the response instrument show adequate model fit. Of all attitude components, ‘affect' appears to be the best predictor of reading behavior. Response factors appear to be structured in two secondary order factors: ‘trance' and ‘literary interpretation'. Attitude and response scores diminish with age. Literary education lessons appear to slow down the diminishing trends. The text experience method seems especially promising for stimulating literary response and attitude toward reading fiction.